The Demands of Madrasah Management Transformation: Strategies to Realize Quality Madrasas Climate - Susanto Susanto; Ayu Desrani; Apri Wardana Ritonga (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine the madrasa management strategy in creating a quality madrasa climate to improve the quality of Islamic education in Indonesia. The research method used is a mixed method, namely by combining quantitative and qualitative data. Quantitative data is in the form of the percentage of madrasa climate implementation. Qualitative data is in the form of descriptions of respondents' perceptions of the use of the madrasah climate. Respondents in this study were madrasa heads, educators, and employees in the madrasa environment, totaling 68 people. These respondents came from 7 provinces in Indonesia who were randomly selected based on region (cluster random sampling). Researchers analyzed quantitative data from the results of the questionnaire descriptively. Meanwhile, qualitative data analysis uses the Miles Huberman model. The results of this study indicate that 89.7% of respondents improve the quality of education services to produce a quality madrasah climate. There are 83.8% of madrasas that have the characteristics of forming a positive madrasa climate such as forming an Islamic culture, improving skills, developing students' interests and talents, and paying attention to character values. The implementation of this strategy is the result of collaboration between madrasa heads, educators, staff, and students. This is indicated by the successive percentages of 92%, 92.6% and 85.3%. The findings of this study reveal that the formation of a quality madrasah climate does not give up the values of religious moderation in the actualization of religion for students in the midst of religious pluralism in Indonesia.